Facilities management of public hall / Mohd Hamidi Ali - Ali, Mohd Hamidi (Faculty of Architecture, Planning and Surveying, 2009)
The use of facilities management has now spread from the public sector to the private sector. Facilities management is an integrated strategy for business support services and buildings-in-use, covering the management of environment, space, support services and information. In the public sector, it is promoted as offering value for money in public services, while in the private sector it is promoted by the changes arising from concentration on core activities. Growing demand has led to the development of new facilities management solutions, including total facilities management and intelligent buildings. This dissertation focuses facilities management on public facilities which is public hall. Public hall is one important facility to a community in certain area whether in town area or in rural area. It becomes a meeting place between people, place to carry out social activity such as wedding ceremonies and so forth. So, it is important to ensure the building and facilities in public halls always in good and perfect condition.